2022
DOI: 10.3389/feart.2022.994258
|View full text |Cite
|
Sign up to set email alerts
|

The spatio-temporal distribution and transport of suspended sediment in Laizhou Bay: Insights from hydrological and sedimentological investigations

Abstract: Suspended sediment transport and deposition are crucial physical processes controlling the geomorphological evolution of estuaries and bays. Specially, under the context of worldwide coastal erosion, knowledge of the spatio-temporal distribution of suspended sediment concentration (SSC) and its associated sediment load have become increasingly important for bay management. However, our understanding of the mechanisms of suspended sediment dynamics continues to be hampered by the lack of high-resolution observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Furthermore, during the flying-over of the satellite on 12 October 2022, the wind speed in most of Laizhou Bay was less than 5 m/s, while on 12 November 2021, the wind speed was higher than 6 m/s (Figure 8). Previous research findings have consistently demonstrated that the dispersion patterns of suspended sediments are influenced by the dynamics of tidal currents [37,38]. Variations in suspended sediment concentrations are primarily induced by seasonal oscillations in sea surface elevation and wind-induced waves [39], with tidal level fluctuations regarded as short-term variations in sea surface elevation.…”
Section: Spatiotemporal Characteristics Of Sscmentioning
confidence: 92%
“…Furthermore, during the flying-over of the satellite on 12 October 2022, the wind speed in most of Laizhou Bay was less than 5 m/s, while on 12 November 2021, the wind speed was higher than 6 m/s (Figure 8). Previous research findings have consistently demonstrated that the dispersion patterns of suspended sediments are influenced by the dynamics of tidal currents [37,38]. Variations in suspended sediment concentrations are primarily induced by seasonal oscillations in sea surface elevation and wind-induced waves [39], with tidal level fluctuations regarded as short-term variations in sea surface elevation.…”
Section: Spatiotemporal Characteristics Of Sscmentioning
confidence: 92%
“…Tides can change the flow cycle mode in the YRE, resulting in different sediment transport patterns (Shan et al, 2004). The diffusion characteristics of suspended sediment in the YRE and its offshore region are controlled by the tidal current field (Xie et al, 2022). Sediment in the no-tide scenario mainly accumulates at the river mouth and diffuses toward the northwest with a small spread range (Figure 11D), then it flows along the YRE coast with the tidal current (Figure 11A).…”
Section: The Dominant External Forcing Of Sediment Distributionmentioning
confidence: 99%